(untitled) (Eurasian Journal of Philology Science and Education, 2026)
The article examines the transcultural space of I.A. Odegov’s novella “The Winged Bride of Mahdi” as a characteristic example of Kazakhstan’s Russian-language literature. Drawing on contemporary theories of transculturality (W. Welsch, H. Bhabha, U.M. Bakhtikireeva, E.F. Shafranskaya, and others), the analysis interprets the novella as an artistic model in which various cultural codes, forms of collective memory, and elements of local Kazakh tradition interact. The study highlights the convergence of urban and steppe cultures, the coexistence of traditional and modern worldviews, and the role of the mediator–observer situated at the cultural boundary. Special attention is paid to linguistic hybridity, cultural archetypes, the chronotope, and narrative images shaping transcultural artistic reality. It is shown that I.A. Odegov’s novella functions as a space of cultural hybridization and dialogue, reflecting the distinctive nature of Kazakhstan’s contemporary literary process. The article substantiates the thesis that transculturality in the text is realized not only at the thematic level but also at the structural-poetic level, thereby forming a distinctive system of artistic meanings. The findings may be applied in further research on Kazakhstan’s Russian-language literature as well as in teaching courses on contemporary literature and theories of transculturality. Keywords: transculturality, Russian-language literature, I.A. Odegov, borderland literature, dialogue of cultures.